Platelet-to-Lymphocyte Ratio: A Novel Prognostic Factor for Prediction of 90-day Outcomes in Critically Ill Patients With Diabetic Ketoacidosis. Issue 4 (January 2016) - Liu, Wen-Yue; Lin, Shi-Gang; Wang, Li-Ren; Fang, Chen-Chen; Lin, Yi-Qian; Braddock, Martin; Zhu, Gui-Qi; Zhang, Zhongheng; Zheng, Ming-Hua; Shen, Fei-Xia
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Diabetic ketoacidosis (DKA) is a life-threatening acute complication of diabetes mellitus and the novel systemic inflammation marker platelet-to-lymphocyte ratio (PLR) may be associated with clinical outcome in patients with DKA. This study aimed to investigate the utility of PLR in predicting 90-day clinical outcomes in patients with DKA. Patient data exacted from the Multiparameter Intelligent Monitoring in Intensive Care II (MIMIC II) database was analyzed. A cutoff value for PLR of 267.67 was determined using Youden index ( P < 0.05) and used to categorize subjects into a high PLR group and a low PLR group. The hazard ratios (HRs) and 95% confidence intervals (CIs) for DKA were calculated across PLR. Clinical outcomes in our study were defined as intensive care unit (ICU) 90-day readmission and all-cause mortality. A total of 278 ICU admissions were enrolled and stratified by cutoff value of PLR. The incidence of readmission and mortality was 17.8% in the high PLR group, significantly higher than 7.4% in the low PLR group. In the multivariable model, after adjusting for known confounding variables including clinical parameters, comorbidities, laboratory parameters, the HRs for DKA were 2.573 (95% CI 1.239–5.345; P = 0.011), 2.648 (95% CI 1.269–5.527; P = 0.009), and 2.650 (95% CI 1.114–6.306; P = 0.028), respectively. The Kaplan–Meier survival curve showed that a high PLR level was associated with a higher risk for 90-day outcomes in patients with DKA. The authors report that higher PLR presents a higher risk for 90-day incidence of readmission and mortality in patients with DKA. It appears to be a novel independent predictor of 90-day outcomes in critically ill DKA patients in ICU units.